Implementación de un sistema informático para la toma de decisiones a los procesos de marketing y ventas de almacén Carlitos del cantón La Maná aplicando herramientas de business intelligence. - Condoy Espinoza, Brillyth Yomara (2022)
Business Intelligence (BI) is a discipline that deals with large volumes of data through specialized technological tools to provide graphic and understandable information to managers of company departments. The applicability of BI depends on the data amount that a company can provide for analysis and interpretation. The company Carlitos has been having problems related to the stagnation in its sales for some time. Based on this information, this research aims to implement a computer system applying Business Intelligence tools for decision-making in the company's marketing and sales processes. To fulfill this objective, bibliographic methods have been employed to demonstrate the basic and necessary concepts from scientific bibliographic sources. Interviews and surveys were also taken into consideration to get a deeper and clearer idea of the problems and identify the requirements. As a result, by applying the Hefesto v2 methodology, it was possible to develop a business intelligence system by using the Microsoft Power BI tool; it can be viewed through a link placed on an advertising and informative web page that allows control of the entry and display of embedded graphic and interactive reports. Finally, it can be concluded that the implementation of the Business Intelligence tool in the company directly helps in making decisions on the sales and marketing department based on its background data.